Is robotic‐assisted ventral mesh rectopexy superior to laparoscopic ventral mesh rectopexy in the management of obstructed defaecation?. (29th August 2013) - Mantoo, S.; Podevin, J.; Regenet, N.; Rigaud, J.; Lehur, P.‐A.; Meurette, G.
Abstract Aim Function, morbidity and recurrence of symptoms after robotic‐assisted ventral mesh rectopexy (RVMR) and laparoscopic ventral mesh rectopexy (LVMR) for pelvic floor disorders (PFDs) were compared. Method Forty‐four patients operated on for PFD with RVMR were compared with 74 of 144 patients who had had LVMR performed between 2008 and 2011. The groups were matched for age, body mass index, American Society of Anesthesiologists status and previous hysterectomy. The same surgical technique and type of mesh were used. Early postoperative morbidity and function [obstructed defaecation syndrome (ODS), incontinence scores (CCF) and sexual activity] were compared. Results Operation time was longer in RVMR compared with LVMR (191 ± 26 vs 163 ± 39 min; P = 0.0002). RVMR showed less blood loss (8 ± 34 vs 42 ± 88 ml; P = 0.012) and fewer early complications (2% vs 11%; P = 0.019). ODS and CCF scores improved in both groups. Patients after RVMR reported a better improvement in digitation, straining and satisfaction after defaecation. There was a statistically significant difference in the postoperative ODS score in favour of RVMR (P = 0.004). Sexually active patients in both groups reported a similar improvement. There was no difference in early recurrence (P = 0.692). Conclusion Although not a randomized comparison, this study shows that ventral mesh rectopexy performed by the robot was followed by better function then LVMR.